Constructive side-channel analysis and secure design : 6th International Workshop, COSADE 2015, Berlin, Germany, April 13-14, 2015. Revised selected papers /: 6th International Workshop, COSADE 2015, Berlin, Germany, April 13-14, 2015. Revised selected papers. (2015) - Unknown
No abstract available